The Effects of Mind Mapping Strategies on the Development of Writing Skills of Selected Form Three Students - K. Amar Singh, Jasvir Kaur (2004)
Education is one of the most powerful mechanisms for developing intellectual prowness. Because the research in brain growth, development and functioning is exemplifying our understanding of the neuro-sciences. In order to nourish students with healthy learning strategies, this research is based on a technique that will prove to enhance students’ thinking and writing skills. This study intends to expose students to the approaches and methods of using mind maps and brainstorming strategies in developing their mental capacities. The research design used in this study was a nonrandomised control group; pretest-posttest quasi-experimental design on to groups of hetrogenous form three Malay students selected based on their form two final year examination academic performance on two classes of students (25 students in the control group and 25 students in the experimental group). The instruments used were pretest composition questions and post-test composition questions, direct observations and in-depth interviews. The data and results collected were analysed using the SPSS for percentage, mean, standard deviation, t-tests and repeated- measures analysis of variance. The finding showed that there was no significant difference in the mean scores in the pretest between the two groups of subjects administered in the first semester of 2002 after the teaching of composition in the normal method. However, there was a significant difference in the mean scores in the experimental group as compared to the control group in the post-test admistered in the second semester of 2002 after the treatment. The findings also showed that the subjects in the experimental group responded more positively to the technique of mindmapping and brainstorming. This study concluded that the teaching method, mindmapping and brainstorming strategies during the prewriting stage had a positive and consistent effect on this group of from three students’ composition writing skills immediately after treatment as compared to the control group with the normal classroom teaching method